Bloodfire, baby : a novel - Carson, Eirinie (Dutton, 2026)
"Before the shadow appeared, Sofia thought mothering would be all sun-drenched light and white linen sheets, as seen advertised by the momfluencers of Instagram. In her gorgeous home anchored in a posh suburb, far removed from her origins, Sofia revels in her success. Motherhood seems like the natural next step, but when her husband travels for a work trip, leaving Sofia all alone with their unnamed three-week-old baby, she can't quite square how mothering falls solely in her lap. Nobody seems able or willing to help her: not her husband, not her best friend, and certainly not the zealot mother she cut off long ago. Her postpartum reality is overtaken by an ominous figure. Sleep-deprivation collides with a darkness that creeps in and begins to spread, threatening to consume her entirely. As her grip on reality slips away, Sofia learns of an insidious haunting that has plagued the eldest daughters in her family for generations. With her baby's safety on the line, Sofia realizes she must confront her murky history or risk losing more than just the veneer of perfection"-- Provided by publisher.